Insights Into the Function and Clinical Application of HDAC5 in Cancer Management - Yang, Jun; Gong, Chaoju; Ke, Qinjian; Fang, Zejun; Chen, Xiaowen; Ye, Ming; Xu, Xi (Frontiers in Oncology, 2021)
Histone deacetylase 5 (HDAC5) is a class Ⅱ HDAC. Aberrant expression of HDAC5 has been observed in multiple cancer types, and its functions in cell proliferation and invasion, the immune response, and maintenance of stemness have been widely studied. HDAC5 is considered as a reliable therapeutic target for anticancer drugs. In light of recent findings regarding the role of epigenetic reprogramming in tumorigenesis, in this review, we provide an overview of the expression, biological functions, regulatory mechanisms, and clinical significance of HDAC5 in cancer.